The effect of prayer beads therapy on lowering blood pressure in hypertensive patients - Anwar, Tabihul; Kosasih, Cecep Eli; Pramukti, Iqbal; Bisri, Dewi Yulianti (Universitas 'Aisyiyah Yogyakarta, 2024)
Hypertension is a condition of a person's blood pressure above the normal number of 120/80 mmHg. Currently, the role of nurses in the development of nursing interventions is one of which is to develop sharing supporting interventions to overcome hypertension problems Management of nonpharmacological hypertension is considered important and can be an alternative such as prayer beads to overcome hypertension including through emotional management so that it can make the body always in a relaxed and calm state. This study aims to determine the effect of prayer beads therapy on data pressure in hypertensive patients. The research method used a quasi experimental pre and post-design with the control group. Consisting of the intervention group and the control group, the number of samples was 24 samples with 12 respondents of the therapeutic intervention group and 12 respondents of the control group, using a simple random sampling technique. The results of this study are the statistical results of the Dependent T test for systolic blood pressure results of p = 0.001 (p < 0.05) and the Dependent T-test statistical results for diastolic blood pressure results of p = 0.001 (p < 0.05). Conclusion: then it can be concluded that there is an effect of prayer beads on decreasing systolic and diastolic blood pressure results in the intervention group. Therapy Beads can be used as a solitary nursing self-intervention to lower Blood Pressure in Hypertensive Patients